Managing Media Relations: Determining the Reputation of Land Grant Institutions from the Perspective of Media Professionals - Lauri M. Baker; Katie Abrams; Tracy Irani; Courtney Meyers (Journal of Applied Communications, 2011)
In recent years, the land grant university has struggled with public awareness outside of its traditional audiences, indicating a potential disconnect between the general public and the media. The purpose of this study was to assess the perceptions and awareness of media with regard to the image and reputation of the University of Florida’s Institute of Food and Agricultural Sciences (UF/IFAS). A sample of 150 state and local media professionals was surveyed to assess perceptions and awareness of UF/IFAS. The results indicated that the media’s perceptions of UF/IFAS image and reputation were positive, but their awareness of the institution’s range of program areas was low. Media professionals consider the information provided by UF/IFAS to be credible, useable, and newsworthy. Respondents said the environment, followed by disaster preparation and recovery were the most important topics to their target audience, while the least important topics to their target audience were 4-H youth development and agriculture. Media professionals were more likely to use UF/IFAS as a source for agriculture and natural resource topics than other topics. Other universities should consider conducting similar research to develop a body of knowledge on media relations at land grant institutions.
Keywords: f UF/IFAS; public awareness; credible; Media professionals; newsworthy; land grant institutions; universities